Implementing program management : templates and forms aligned with the standard for program management, and other best practices - Levin, Ginger; Green, Allen R. (Boca Raton : CRC Press, 2014)
Success in program management requires discipline, complete plans, well-run meetings, accurate record keeping, and adherence to global best practices. This book provides the templates and guidelines for the plans, forms, agendas, registers, and procedures you will need. Ginger Levin and Allen Green wrote Implementing Program Management Templates and Forms Aligned with the Standard for Program Management - Second Edition (2008) in 2010.
Includes bibliographical references and index.
usc 25/10/17
Loans
Keywords: Project management